Applications Various Extracts of Plant On Stem Growth Response of Red Dragon Fruit (Hylocereus polyrhizus) - Sanjaya, Wiwit; Indratmi, Dian; Sufianto, Sufianto (Universitas Muhammadiyah Malang, 2019)
This study aims to determine the response of the growth of red dragon fruit stem cuttings (Hylocereus polyrhizus) with the treatment of various plant extracts and dosage of goat manure. This research was conducted in experimental garden of UMM. This research was conducted from October 2017 until January 2018. The study used a randomized block design, which was repeated 3 times with 2 factors. Factor 1 is a kind of plant extract and factor 2 is the dosage of manure. Factor 1 consists of 4 level, while factor 2 that consists of 3 level. Observation parameters include: Shoots, shoot number, shoot length, root length, root number, total wet weight, shoot dry weight, wet root weight, and root dry weight. The results showed that the treatment of green bean sprout extract and dose 187.5 g / polybag showed the best result on the number of shoot and wet weight of cuttings. Treatment of green bean sprout extract showed relatively good results. Treatment of fertilizer doses of 187.5 g / polybag showed relatively good results.